2021
DOI: 10.1111/jmwh.13231
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Exposure Prophylaxis for HIV Infection and the Role of the Women's Health Care Provider in HIV Prevention

Abstract: HIV infection is a major public health problem for women in the United States. Prevention of new HIV infections is essential to the goal of eliminating HIV in the United States. Pre‐exposure prophylaxis (PrEP) is an effective and safe HIV prevention method recommended for women at increased risk for HIV infection, including during pregnancy and lactation. The recommended PrEP regimen is a fixed‐dose combination of tenofovir disoproxil fumarate and emtricitabine administered as a single daily dose. The initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(110 reference statements)
2
1
0
Order By: Relevance
“…Similarly, Nicole De Wet's research in South Africa (2019) found that young women, especially those aged 20-24 and students, were more likely to choose older partners for financial benefits [26]. This underscored the complex interplay of emotional, highlighted the role of women's healthcare providers in HIV prevention resonating with our findings in Chad [31].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similarly, Nicole De Wet's research in South Africa (2019) found that young women, especially those aged 20-24 and students, were more likely to choose older partners for financial benefits [26]. This underscored the complex interplay of emotional, highlighted the role of women's healthcare providers in HIV prevention resonating with our findings in Chad [31].…”
Section: Discussionsupporting
confidence: 76%
“…Studies like Wathuta (2016) emphasize the need for accurate gender dynamics representation in HIV responses [30]. Moreover, Ruppe et al (2021) highlighted the role of women’s healthcare providers in HIV prevention resonating with our findings in Chad [31].…”
Section: Discussionsupporting
confidence: 51%
“…We also need to increase utilization of prevention strategies for diseases like HIV for which no vaccines exist. Ruppe 7 discusses how pre‐exposure prophylaxis for HIV infection is an underutilized yet feasible approach to protect individuals at higher risk of HIV infection. The articles by Pesch about cytomegalovirus 8 and by Hunter about parvovirus B‐19 9 highlight the importance of hygiene practices in protection against perinatal transmission through body fluids and respiratory droplets.…”
mentioning
confidence: 99%